(untitled) (Вісник: Міжнародні відносини, 2024)
This article examines the current state of cloud solution adoption across banking industry. While the advantages of using cloud are clear, this process introduces new challenges and risks. Considering security as the most important obstacle to cloud adoption for bank institutions, it’s highlighted the specific of operation cloud models more suitable to meet the needs of digital banks. The reasons for migration of core workloads to the cloud are also outlined. It reflects the increasing impact of cloud technology on the modern business models across banking industry in the new digital economy.